Mental wellness chatbot application for mental health peer supporters (B) - Tan, Wei Zheng (Nanyang Technological University, 2023)
Mental health is a crucial aspect of overall health and well-being, yet it remains a largely neglected topic in society. Despite the growing awareness of mental health issues, there remains a significant stigma surrounding mental health, preventing many individuals from seeking help or support. Therefore, it is essential to focus on improving mental health services and support to address these issues and provide individuals with the resources and assistance they need to achieve optimal mental well-being. This project aims to create an application with a chatbot, for peer supporters, with higher intelligence responses compared to those chatbots that are currently in the market and a forum page for peer supporters to share their thoughts or useful information to fellow peer supporters. This application mainly aims to equip peer supporters with the necessary resources and support while managing their personal well-being. The application was developed on Android Studio Integrated Development Environment (IDE) while using Flutter framework and Firebase services, and chatbot uses Google Dialogflow.